2018
DOI: 10.1016/j.jacc.2018.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent and Incident Heart Failure in Cardiovascular Outcome Trials of Patients With Type 2 Diabetes

Abstract: Despite multiple examples of glucose lowering therapies affecting heart failure (HF) risk, ascertainment of HF data in cardiovascular outcome trials of these medications has not been systematically characterized. In this review, large (N >1,000) published phase III/IV cardiovascular outcome trials evaluating glucose lowering therapies through June 2017 were identified. Data were abstracted from publications, Food and Drug Administration (FDA) Advisory Committee records, and FDA labeling documents. Overall, 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…Despite this robust evidence, HF seems to have been neglected by clinicians and scientists who dedicate more attention to the atherothrombotic complications of diabetes. HF remains one of the most common and serious complications of diabetes and is, in fact, as common as the occurrence of ischemic events, with perhaps even higher rates . HF in the context of diabetes mellitus is attributed to macrovascular and microvascular dysfunction, volume overload, impaired renal function and the direct effects of diabetes mellitus and insulin resistance on cardiac myocytes .…”
Section: Hf Risk Has Not Changed Despite Improvement In CV Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this robust evidence, HF seems to have been neglected by clinicians and scientists who dedicate more attention to the atherothrombotic complications of diabetes. HF remains one of the most common and serious complications of diabetes and is, in fact, as common as the occurrence of ischemic events, with perhaps even higher rates . HF in the context of diabetes mellitus is attributed to macrovascular and microvascular dysfunction, volume overload, impaired renal function and the direct effects of diabetes mellitus and insulin resistance on cardiac myocytes .…”
Section: Hf Risk Has Not Changed Despite Improvement In CV Outlookmentioning
confidence: 99%
“…HF remains one of the most common and serious complications of diabetes and is, in fact, as common as the occurrence of ischemic events, with perhaps even higher rates. 17 HF in the context of diabetes mellitus is attributed to macrovascular and microvascular dysfunction, volume overload, impaired renal function and the direct effects of diabetes mellitus and insulin resistance on cardiac myocytes. 18 Unfortunately, more traditional glucose-lowering agents have not proven to be effective in reducing HF risk in patients with T2D.…”
Section: Advance (Action In Diabetes and Vascular Disease: Preterax Andmentioning
confidence: 99%
“…Despite the tremendous advancement of science and the establishment of new therapeutic targets in type 2 diabetes mellitus care, the capture of heart failure−specific information in completed CVOTs has been limited. 5 In a recent systematic review 5 of large CVOTs of major therapeutic programs in type 2 diabetes mellitus, heart failure at baseline and during follow-up was infrequently defined. When provided, only a subset of patients enrolled carried a baseline history of heart failure, ranging from 1% to 28% across trials.…”
Section: Caveats Of Completed Cvotsmentioning
confidence: 99%
“…4 In the last decade, more than 20 largescale CVOTs enrolling more than 150,000 randomized patients have been conducted (Figure 1). 5 Nearly all these clinical trial programs have studied a primary endpoint of major adverse cardiovascular events (MACE), namely nonfatal myocardial infarction, nonfatal stroke, and cardiovascular death; heart failure has infrequently been included as a primary or secondary clinical endpoint in CVOTs. 5 In this review, we discuss the central importance of heart failure as a therapeutic endpoint in type 2 diabetes mellitus care, particularly in the context of the sodium-glucose co-transporter 2 (SGLT2) inhibitor class of glucose-lowering therapies.…”
Section: Introductionmentioning
confidence: 99%
“…According to over 40 clinical trials conducted from 1999 to 2007, rosiglitazone has been reported to increase risks of heart failure [13,14] and myocardial infarction in T2DM patients [15][16][17]. Additionally, rosiglitazone was associated with a significant increase in the risk of death from cardiovascular causes that had borderline significance [13,16,18,19]. Rosiglitazone may also worsen the clinical course in patients with pre-existing left ventricular dysfunction [20].…”
Section: Introductionmentioning
confidence: 99%